Perancangan protytipe sistem pengendali kadar gas karbon monoksida pada area bengkel mobil - Umar Nur Wanto; Indra Riyanto (MAESTRO, 2019)
In this final project, a system for controlling air circulation in the car workshop area with a control PID be designed. This system consists of Arduino Mega2550, 4 CO MQ7 gas sensors, motor drivers, 2 fan motors, LCD, 2 LED lights, and Buzzer. The method used for system controllers is the PID control. The system gets input from the CO MQ7 gas sensor. Where the sensor reads the presence of smoke and CO gas in the car workshop area. The output produced by the PID control system is a Pulse Width Modulation (PWM) signal which is then used by the motor driver to adjust the rotation speed of the fan motor. The rotation of the fan motor will regulate air circulation in the controlled system area. PID controllers use parallel structures with parameters Kp, ki and kd obtained by trial and error method. In the overall test using PID parameters at the values of Kp = 3.5, Ki = 0.025, and Kd = 0.5 shows that it can save electricity energy more by 65.16 % compared to full speed fan testing. Keywords— Parameter, PWM, Gas CO, control PID, Trial and error.